PENGARUH FAMILY PSYCHOEDUCATION TERHADAP PENINGKATAN PENGETAHUAN DAN PENURUNAN KECEMASAN KELUARGA DALAM MERAWAT PENDERITA KANKER SERVIKS DI RSUD DR. MOEWARDI SURAKARTA - Dian Anisia Widyaningrum* Titin Andri Wihastuti** Tina H.Nasution*** (The Indonesian Journal of Health Science, 2015)
Cervical cancer is the cancer most of Indonesia's first and most deadly sufferer. Anxiety often occurs in families who care for patients with cervical cancer because of fear of loss and frustration can not do much business. Lack of knowledge related to the treatment and prognosis of the disease is also a stressor for families. Nurses can reduce the impact of family therapy with psychoeducation. The purpose of this study, wanted to know the effect of family psychoeducation to increase knowledge and decrease family anxiety in treating patients with cervical cancer. This study design is quasi-experimental (Quasy Experiment) with non randomized control group pretest posttest. The population of all families who care for family members with cervical cancer at the Hospital Dr. Moewardi Surakarta. The total sample of 28 respondents, drawn from that meet the inclusion criteria, and methods of non-probability sampling is purposive sampling. The independent variable is the treatment of family psychoeducation and the dependent variable is the level of knowledge and family anxiety. The data collected using questionnaires pretest and posttest on respondents. Then analyzed by Wilcoxon and Man Whitney test and significant when ρ 0.05. Results showed no effect of family psychoeducation to increase knowledge with ρ = 0.002 and decreased anxiety families with ρ = 0.001. Therefore, every nurse souls should implement family psychoeducation in family therapy who have less knowledge and anxiety in the hospital.